Komplexní marketingová strategie v online prostředí - Novák, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Práce má za cíl poskytnout základní přehled marketingových koncepcí a nástrojů využitelných pro prostředí Internetu, zmapovat aktuální trendy v online prostředí a aplikovat je na konkrétní řešení komplexní marketingové strategie. Výstupem práce je návrh účinné strategie pro pánský lifestyle magazín, který bude vyžadovat jen minimální finanční zdroje. Účinnosti strategie bude dosaženo vhodnou kombinací a aplikací nástrojů využitelných v online prostředí. Nosným prvkem strategie bude synergický soulad jednotlivých částí marketingového mixu pro jeho maximální efektivitu a minimální náklady.

This thesis provides basic overview of marketing concepts and tools which are available for the Internet environment. It also provides new trends and opportunities in the online environment. Output of the thesis will be efficient strategy for men's lifestyle magazine with usage of minimum finance sources. Eficiency will be taken by using of combination and application of marketing tools available in the Internet environment. The main goal is to get super-synergy affect of marketing mix components for maximum efficiency and minimum costs.
Complex Marketing Strategy in the Internet Environment
Keywords: Internet marketing; strategie; plánování; cílení; segmentace; marketingový mix; online; 4S; sociální sítě; viralita; SEO; SEM; PPC; PR; brand management; affiliate marketing; lead generation; barter; webová analytika; měření; landing page; real-time optimalizace; e-business; ROI; synergie; portál; Internet marketing; strategy; planning; targeting; segmentation; marketing mix; online; 4S; Social networks; virality; SEO; SEM; PPC; PR; brand management; affiliate marketing; lead generation; barter; web analytics; metrics; landing page; real-time optimization; e-business; ROI; synergy; portal